Peran Ulama Desa Teluk Meku Dalam Menanggulangi Praktik Nikah Siri - Joko Satria; Muhmmad Saleh; Diyan Yusri (Journal Smart Law, 2023)
The Siri Marriage legal system in Indonesia does not recognize the term "Siri Marriage" and the like, and does not specifically regulate it in a constitutional regulation. This term is given to marriages that are not registered and are considered to have been carried out without fulfilling the provisions of the law, particularly regarding the registration of marriages as regulated in Law no. 1 of 1974 concerning marriage contained in article 2 paragraph 2 which states that "Every marriage is recorded according to the applicable laws and regulations" all this is done in order to avoid what is called harm. So the role of the Ulama is a figure who has a charismatic aim to broadcast Islam to people's lives so that they carry out God's commands and stay away from God's prohibitions and are highly trusted and make role models by the community to build Islamic civilization so that people's lives are Islamic and consistent with their religion in accordance with Al- Qur'an and Hadith of the Prophet Muhammad and have an impact on the behavior of the social life of the community. Based on this analysis, it can be seen that marriage is not enough just to have an oral contract between the two parties (the prospective groom and the prospective bride), but what is far more important is to record the marriage contract so that valid written evidence can be obtained. . With this evidence, the couple can avoid harm in the future because this written evidence (in the form of a marriage certificate) can legally process various household issues, especially as the most powerful evidence in a religious court.